Field-based physical fitness assessment in preschool children: A scoping review - Ke, Dandan; Maimaitijiang, Remili; Shen, Shaoshuai; Kishi, Hidetada; Kurokawa, Yusuke; Suzuki, Koya (Frontiers in Pediatrics, 2022)
Physical fitness, that can be measured using various health- and skill-related components, is an important indicator of child development and health status. This study summarizes the most widely used field-based physical fitness batteries and specific test items for preschool children. A search of literature in English was undertaken using two major electronics databases, which yielded 76 literatures that met the inclusion and exclusion criteria. This review found that of these 76 literatures analyzed, 71.1% came from Europe and 89.5% were published after 2010. The results showed six physical fitness test batteries, with the assessing fitness in preschoolers (PREFIT) battery being most widely used, and specific test items such as BMI, standing long jump, handgrip, one-leg stance, sit and reach, 20 m SRT-PREFIT, and 4×10 m SRT are widely used in corresponding components. Therefore, we recommend that an international standard for some specific test items should be developed for preschool children to facilitate more widespread adoption and promote physical fitness assessment for preschool children.